(untitled) (Research, Society and Development, 2025)
Cemento-Ossifying Fibroma (COF), classified among Fibro-Osseous Lesions (FOL), is considered a benign odontogenic neoplasm of mesenchymal origin with significant growth potential. This study aims to report a clinical case of COF treatment in the maxilla and its postoperative clinical evolution. A 20-year-old male patient presented with facial swelling with a one-year evolution and a diagnosis of FOL from a biopsy performed at another facility. On extraoral physical examination, a hard, right maxillary mass was observed. Intraoral examination revealed slight buccal expansion in the ipsilateral maxillary vestibule. Imaging studies showed a well-defined mixed lesion extending from the canine to the first molar on the right side. Based on clinical, imaging, and histopathological data, the diagnosis of COF was confirmed. Surgical treatment was performed under general anesthesia via an intraoral approach, resection with a small safety margin, and reconstruction of the bone defect using a titanium mesh covered with a pedicled flap from the buccal portion of Bichat’s fat pad. The patient has now undergone two years of postoperative follow-up, with no complaints or signs of recurrence and rehabilitated with a removable partial denture. Distinguishing COF from FOL poses a significant challenge, as both exhibit histological similarities and a range of clinical and radiographic findings. A detailed evaluation is essential to ensure an accurate diagnosis and appropriate treatment.